Pengaruh Pemberian Arang Sekam Padi dan Kompos Trichoazolla terhadap Pertumbuhan dan Hasil Tanaman Padi Gogo (Oryza sativa L.) di Lahan Gambut - Andrhea. G, Batara Ariaus; Ariani, Erlida; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to determine the effect of rice husk charcoal and trichoazolla compost on growth and production of upland rice and to obtain the best combination of treatments. This research was conducted at Agriculture Experimental Station of Agriculture Faculty of Riau University, Rimbo Panjang Village, Tambang Sub District, Kampar Regency from January to April 2017 by using Completely Randomized Design (CRD) consisting of 2 factors and 3 replications. The first factor is T0: without rice husk chacoal, T1: Rice husk charcoal 2,5 t.ha-1, T2: Rice husk charcoal 5 t.ha-1 and T3: Rice husk charcoal 7,5 t.ha-1. The second factor was P1: Trichoazolla compost 3 t.ha-1, P2: Trichoazolla compost 6 t.ha-1 and P3: Trichoazolla compost 9 t.ha-1. The results of this research indicate that the interaction of husk rice and trichoazolla compost increases growth and yield of upland rice plants and is seen in the number of all tillers, number of productive tillers, plant height, panicle length, percentage of pithy rice and weight of 1000 grains of grain. Grams of rice husks 5 t.ha-1 and compost trichoazolla 6 t.ha-1 are the best doses. Keywords: rice husk charcoal, trichoazolla compost, gogo rice, peat land.